2022
DOI: 10.1111/ejh.13742
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of immune cell and cytokine signalling correlates with clinical outcomes in myelodysplastic syndrome (MDS)

Abstract: Novelty Statements: 1.What is the NEW aspect of your work? This study utilises correlative samples collected across 3 prospective clinical trials in MDS conducted in Australia (LEN-SCF, ALLG MDS3 and ALLG MDS4 clinical trials) and uses novel methods for analysing immune cell subsets which correlated with clinical outcomes in MDS. What is the CENTRAL finding of your work?The main findings from this study are that dysregulation in innate immunity and inflammatory signalling play central roles in the pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Cytokine-cytokine receptor interactions have been reported as a major pathway enriched in MDS, with miR-221 similarly identified in this study as a key miRNA modulating this pathway, in addition to miR-30b and miR-30e (24). Consistent with this observation, we have previously reported that the gene expression analysis from BM colonyforming units of MDS patients that have normalized after four cycles of treatment, exhibiting the downregulation of cytokine signaling (25).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Cytokine-cytokine receptor interactions have been reported as a major pathway enriched in MDS, with miR-221 similarly identified in this study as a key miRNA modulating this pathway, in addition to miR-30b and miR-30e (24). Consistent with this observation, we have previously reported that the gene expression analysis from BM colonyforming units of MDS patients that have normalized after four cycles of treatment, exhibiting the downregulation of cytokine signaling (25).…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, Patient No these similar pathways were observed in this study as key regulatory players in driving AA clonal progression to MDS/AML. We have similarly demonstrated that the MAPK12 gene was upregulated at MDS diagnosis and downregulated in normal BM colonies after four cycles of treatment (25). The Hippo signaling pathway interacts with other growth control and cell proliferation pathways such as PI3-AKT, TGF-b, RAS-MAP kinase, JAK/ STAT, Notch, and Wnt signaling through YAP (Yes-associated protein) activation (28), and the downregulation of miR-9 and miR-550-1 is postulated to contribute to AML pathogenesis through inhibition of their tumor suppressor functions on the Hippo and YAP signaling pathways (29,30).…”
Section: Discussionmentioning
confidence: 68%
“…Related to this proinflammatory milieu that drives the expansion of HSPCs, we have observed that the reduction of nonclassical monocytes is associated with the clinical response to the HMA regimen. Nonclassical monocytes are anti-inflammatory cells that are elevated and functionally impaired in high-risk MDS ( 53, 54 ). Thus, their disbalance might be associated with an overactivation of the proinflammatory signals that will further foster tumor immune escape.…”
Section: Discussionmentioning
confidence: 99%
“…It has a chance to transform to AML, leading to a high risk of patient death. Research revealed that the abnormal immunophenotypic changes of bone marrow cells in MDS were tightly associated with the risk stratification of MDS, AML transformation and prognosis [ 20 22 ]. CD300e which is expressed by monocytes and mDCs can prevent the apoptosis of these two types of cells by triggering intracellular calcium mobilization and inducing the production of superoxide anion O(2)(-).…”
Section: Discussionmentioning
confidence: 99%